Kumpulan Melaka Berhad - Zakariah, Zulhairi (1997)
Kumpulan Melaka Berhad (KMB) is subsidiaries of Melaka State Incorporate which as the group committed to accelerating industrialization and enhanced economic development within and outside the state. KMB was established in 1995 and in the first year KMB has loss which all of operation were no active. In the second year, KMB has net profit RM 561,527 in which 3 then 12 business operation was active. It was amidst these turn of events that KMB had to act swiftly to face these challenges and ensured its continued profitability. Based on SWOT matrix analysis that performed to arrive at the various alternatives viable for KMB. It was founded that KMB was positioned in attractive company and enjoyed competitive advantages in an unstable environment. It was recommended that strategies of KMB is gradually and should to expansion the development operation at the same time to closing down the operation division. KMB needed to ensure effective implementation of its strategies to bear its desired results with commitment by it's top management and facilitated by a conducive structure comprising highly motivate employees.